I CORALLI DEL CALCARE Dl ZU (TRIASSICO SUPERIORE) DELLA LOMBARDIA (ITALIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The present study deals with a detailed taxonomic study Of the Scleractinia from the middle and upper parts of the Calcare di Zu (Zu Limestone), a formation outcropping in the Central Lombardy and dated as Rhaetian (Late Triassic).The specimens examined belong to the Collections of the Natural History of the Cities of Bergamo  and Milano. Some specimens deposited at the Museum in Milano belong to the original collection of Stoppani (figured by this author in 1857 to 1865 papers).According the present revision, the genus Stylophyllopsis Frech, 1890 is a junior synonym of the genus Lepiconus Stoppani, 1857 and Retiophyllia paraclathrata Roniewicz, 1974 is a junior synonym of Retiophyllia langobardica (Stoppani, 1857). The fauna consists of 11 species, belonging to the genera: Cyathocoenia, Astraeomorpha, Pamiroseris, Palaeastraea, Lepiconus, Stylophyllum, Retiophyllia and «Thecosmilia».Some of the identified species are known only from Stoppani Collection. Someothers, instead, have a larger distribution and are recorded from the northern Side of the Alps, from the Tatra Mountains, Iran, Pamir, and from Northern America.
Keywords: Systematics Corals; Scleractinia; Rhaetian; Southern Alps (Italy).